Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping - Goudappagouda; Wakchaure, Vivek Chandrakant; Ranjeesh, Kayaramkodath Chandran; Abhai, Chalona Antony Ralph; Babu, Sukumaran Santhosh (Chemical Communications, 2017)
Light harvesting donor-acceptor assemblies are indispensable to efficiently tap photons. In an attempt to improve the light harvesting efficiency of an acceptor doped assembly, we design and synthesize a donor-acceptor-donor triad which exhibits an exceptional intramolecular energy transfer with excellent efficiency. Moreover, a facile cascade energy transfer (energy funnelling) is observed in the presence of a series of second acceptors (63-91% efficiency) with tunable emission colours. Self-assembled nanosheets formed by the triad in the presence of acceptors exhibit cascade energy transfer assisted tunable emission. In addition, use of chiral acceptors induces chirality to the triad and results in the formation of chiral nanosheets alongwith cascade energy transfer. Here chiral induction, nanosheet formation and cascade energy transfer in the presence of chiral acceptors are used as tools to probe the intercalation of acceptor molecules in the donor scaffold.